2023
DOI: 10.3390/horticulturae9101073
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of One-Year Seed Spaceflight Storage on Yield, Biochemical and Mineral Characteristics of Mature Leafy Vegetables Belonging to Brassicaceae, Apiaceae and Asteraceae Families

Viktor Kharchenko,
Nadezhda Golubkina,
Liubov Skrypnik
et al.

Abstract: Spaceflight is known to produce genetic changes in seeds, usually accelerating aging, though species and varietal differences have been poorly investigated. Comparisons were carried out in terms of yield, biochemical characteristics and mineral composition between mature plants grown from seeds subjected to a one-year spaceflight, belonging to Brassicaceae (Brassica juncea and Eruca sativa), Apiaceae (Anethus graveolens, and Coriandrum sativum), and Asteraceae (Lactuca sativa, six cultivars) families, and non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…Photosynthetic pigment accumulation is closely connected with the intensity of plant development, indicating the efficiency of carbon assimilation. Indeed, the evaluation of the intensity of photo-pigment accumulation in lettuce, Brassicaceae and Apiaceae species grown from the one-year storage of seeds at the ISS demonstrated significant species and varietal differences directly related to plant yield [33]. In the present study, the analysis of photosynthetic pigments showed an increase in the chlorophyll a level only in space-treated cv.…”
Section: Photosynthetic Pigmentssupporting
confidence: 38%
See 2 more Smart Citations
“…Photosynthetic pigment accumulation is closely connected with the intensity of plant development, indicating the efficiency of carbon assimilation. Indeed, the evaluation of the intensity of photo-pigment accumulation in lettuce, Brassicaceae and Apiaceae species grown from the one-year storage of seeds at the ISS demonstrated significant species and varietal differences directly related to plant yield [33]. In the present study, the analysis of photosynthetic pigments showed an increase in the chlorophyll a level only in space-treated cv.…”
Section: Photosynthetic Pigmentssupporting
confidence: 38%
“…Information about the effect of seed spaceflight storage on the mineral composition of mature plants is rather scarce. Indeed, a significant decrease in most minerals was recorded in leafy vegetables grown from spaceflight storage seeds, except Se, whose concentration in space-treated plants was significantly higher than in the control ones [33]. The decrease of iron and copper levels in space-treated tomato fruits were also indicated in another work [49].…”
Section: Elemental Compositionmentioning
confidence: 73%
See 1 more Smart Citation